2012
DOI: 10.1001/archgenpsychiatry.2011.1519
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Prefrontal Cortex γ-Aminobutyric Acid and Glutamate-Glutamine Levels in Schizophrenia Measured In Vivo With Proton Magnetic Resonance Spectroscopy

Abstract: To our knowledge, this study presents the first GABA concentration measurements in unmedicated patients with schizophrenia, who showed elevations in both GABA and Glx levels in the medial prefrontal cortex but not the dorsolateral prefrontal cortex. Medicated patients did not show these elevations, suggesting possible normalization of levels with antipsychotic medication. The Glx elevations agree with prior magnetic resonance spectroscopy literature, but GABA elevations were unexpected and suggest possible inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
152
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(180 citation statements)
references
References 84 publications
24
152
4
Order By: Relevance
“…However, we found an inverse correlation between GABA/Cr ratios and glutamate levels in the parieto-occipital cortex in healthy controls but not in patients. Considering the tight coupling of GABA and glutamate through GAD, this is unexpected and contrasts with previous studies reporting positive correlations between GABA and glutamate in patients in the anterior cingulate and parieto-occipital cortices (Ongür et al, 2010) and in a mixed sample of patients and healthy controls in the prefrontal cortex (Kegeles et al, 2012). …”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, we found an inverse correlation between GABA/Cr ratios and glutamate levels in the parieto-occipital cortex in healthy controls but not in patients. Considering the tight coupling of GABA and glutamate through GAD, this is unexpected and contrasts with previous studies reporting positive correlations between GABA and glutamate in patients in the anterior cingulate and parieto-occipital cortices (Ongür et al, 2010) and in a mixed sample of patients and healthy controls in the prefrontal cortex (Kegeles et al, 2012). …”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, pharmacologically induced NMDA receptor hypofunction causes increases in glutamate levels (Moghaddam et al, 1997). Also, a longitudinal study (De la Fuente-Sandoval et al, 2013) and a cross-sectional study (Kegeles et al, 2012) showed that antipsychotic medication decreases the elevated glutamate levels in the unmedicated state. Altered glutamate levels may be a result of hypofunction of the NMDA-type of glutamate receptor (Olney et al, 1999; Kondziella et al, 2007; Stone et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, it may be the case that this measure does not constitute a sufficiently stringent test of the prediction of reduced GABA in synaesthesia. For example, one reason to doubt the link between GABA and PS/OS ratios in the Yoon et al (2010) study is that patients with schizophrenia were medicated, which may represent an important confound in the measurement of GABA levels in this population (Kegeles et al, 2012). However, it is readily evident that the relationship between GABA and the PS/OS ratio in Yoon et al (2010) is driven by controls, rather than schizophrenics.…”
Section: Discussionmentioning
confidence: 97%